Methodological Nationalism, Migration and Political Theory. (March 2016) - Sager, Alex
The political theory of migration has largely occurred within a paradigm of methodological nationalism and this has led to the neglect of morally salient agents and causes. This article draws on research from the social sciences on the transnationalism, globalization and migration systems theory to show how methodological nationalist assumptions have affected the views of political theorists on membership, culture and distributive justice. In particular, it is contended that methodological nationalism has prevented political theorists of migration from addressing the roles of non-state agents and of transnational economic, social and political structures. These agents and structures contribute to the asymmetrical distribution of goods and opportunities and thus have important implications for debates about migration and distributive justice.